Efectos antioxidantes, fisicoquímicos y sensoriales de mezclas de zumos de bilimbi y sandía en una bebida refrescante - Loor Vera, Heidi Pierina (2024)
The objective of this research was to determine the antioxidant, physicochemical and sensory effects of mixtures of bilimbi juice, watermelon and water with levels 20-30, 40-50 and 30-40 respectively in a soft drink. A Simplex-Centroid Mixture Design with one replicate was used, resulting in 20 experimental units of 1000 mL each. Physicochemical variables (pH, soluble solids and viscosity), microbiological variables (coliforms, fecal coliforms, molds and yeasts), as well as the determination of antioxidant capacity by the ABTS method were evaluated. In addition, a sensory analysis was carried out to evaluate attributes such as color, odor, flavor and texture. The results showed that pH values ranged between 3.16 and 3.92, soluble solids between 13.75 % and 15.45 %, and viscosity between 1.60 and 2.30 mPa.s. All treatments complied with the microbiological standards established by the regulations (NTE INEN 2337). The antioxidant capacity of the soft drink ranged from 1504.3 to 2082.85 μmol Trolox Equivalent/mL. In the sensory test, conducted with untrained tasters, treatment 10 was the preferred treatment in terms of color, odor and flavor, while treatment 7 scored highest in texture. The results obtained indicate that the soft drink made with a combination of 20% bilimbi juice, 45% watermelon juice and 35% water provides the highest levels of antioxidants and complies with the parameters established by current regulations.